The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1111/1744-9987.12170
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Residual Renal Function and Serum Fibroblast Growth Factor 23 in Patients on Peritoneal Dialysis

Abstract: Fibroblast growth factor 23 (FGF23) levels in dialysis patients are influenced by various factors, including phosphorus load. However, the clinical parameters that determine serum FGF23 levels in patients on peritoneal dialysis (PD) remain unclear. The aim of the present study was to examine the effects of clinical factors, on serum FGF23 levels, with an emphasis on residual renal function (RRF). This cross-sectional study included 56 outpatients undergoing PD therapy. Urine volume ≥ 100 mL/day or renal creati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 31 publications
(39 reference statements)
1
7
0
Order By: Relevance
“…Theoretically, dietary P intake should increase sFGF23, whereas P elimination and use of P‐binders decrease sFGF23 by reducing P load; and in fact, P‐binders and dietary P restriction are shown to reduce sFGF23 . We recently showed in a cross‐sectional study that sFGF23 was negatively correlated with RKF . In the present study, we showed that at 18‐months, sFGF23 was negatively associated with baseline renal Cr clearance, and total P elimination at baseline was negatively correlated with sFGF23 increase.…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…Theoretically, dietary P intake should increase sFGF23, whereas P elimination and use of P‐binders decrease sFGF23 by reducing P load; and in fact, P‐binders and dietary P restriction are shown to reduce sFGF23 . We recently showed in a cross‐sectional study that sFGF23 was negatively correlated with RKF . In the present study, we showed that at 18‐months, sFGF23 was negatively associated with baseline renal Cr clearance, and total P elimination at baseline was negatively correlated with sFGF23 increase.…”
Section: Discussionsupporting
confidence: 49%
“…Demographic, clinical, and prescription data at each 6‐month examination were also recorded. Blood, urine, and peritoneal dialysate samples were collected from patients undergoing PD at Kyushu University Hospital every 6 months to evaluate their medical condition, adequacy of dialysis, and peritoneal status . One day before their regular visits, urine and peritoneal dialysate were collected for 24 h at the patients’ homes and the 24 h volumes of urine and peritoneal dialysate were recorded.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Blood, 24‐h urine, and peritoneal dialysate samples were collected from patients undergoing PD at Kyushu University Hospital every 6 months to evaluate their medical condition, adequacy of dialysis, and peritoneal status . Demographic, clinical, and prescription data at each 6 month examination were also recorded based on the guidelines .…”
Section: Methodsmentioning
confidence: 99%
“…Blood, 24-h urine, and peritoneal dialysate samples were collected from PD patients at least every 6 months to evaluate their dialysis and peritoneal status as well as medical condition [11]. Demographic, clinical, and prescription data at each 6-monthly examination were also recorded based on the guidelines [12].…”
Section: Data Collectionmentioning
confidence: 99%